An Innovative 3-phase Design of Multilevel Converter for Renewable Energy Applications - Dr. Meka Sandeep, R. Murali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper a new three phase symmetrical multilevel converter for grid connected system using PV source. The renewable energy sources are application of the distributed generation (DG) in the distribution system acquired more attention. The Distribution generation systems are powered by micro sources such as fuel cells, photovoltaic (PV) systems, and batteries. PV distributed system in which the solar source is low dc input voltage interfaced to grid using front-end conversion. Three phase Cascaded H-Bridge Seven level inverter is interfaced with low frequency transformer with multiplePV Source is proposed. Nowadays multilevel inverter (MLI) plays a vital role in the field of power electronics and being widely used in many industrial and commercial applications. Moreover the advantages like high quality power output, low switching losses, low electro-magnetic interference (EMI) and high output voltage made multilevel inverter as a powerful solution in converter topology.